2004
DOI: 10.21273/jashs.129.3.0407
|View full text |Cite
|
Sign up to set email alerts
|

`Bing' Sweet Cherry on the Dwarfing Rootstock `Gisela 5': Thinning Affects Fruit Quality and Vegetative Growth but not Net CO2 Exchange

Abstract: ADDITIONAL INDEX WORDS. carbohydrate assimilation, fruit to leaf area ratio, photosynthesis, Prunus avium, sink strength, yield ABSTRACT. Canopy fruit to leaf area ratios (fruit no./m 2 leaf area, F:LA) of 7-and 8-year-old 'Bingʼ sweet cherry (Prunus avium L.) on the dwarfi ng rootstock 'Gisela 5ʼ (P. cerasus L. x P. canescens L.) were manipulated by thinning dormant fruit buds. F:LA infl uenced yield, fruit quality, and vegetative growth, but there were no consistent effects on whole canopy net CO 2 exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
78
5
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 40 publications
14
78
5
2
Order By: Relevance
“…Shoots that emerged subsequently from secondary and tertiary buds grew vigorously (most evident in number of leaves per shoot; Fig. 3B), a compensatory growth mechanism that has long been demonstrated in grapevines and other perennial fruit crops (e.g., Candolfi-Vasconcelos and Koblet, 1990;Edson et al, 1995;Petrie et al, 2000;Whiting and Lang, 2004). In grapes, secondary and tertiary buds are known to produce fewer and smaller clusters than do primary buds (Pratt, 1974).…”
Section: Resultsmentioning
confidence: 80%
“…Shoots that emerged subsequently from secondary and tertiary buds grew vigorously (most evident in number of leaves per shoot; Fig. 3B), a compensatory growth mechanism that has long been demonstrated in grapevines and other perennial fruit crops (e.g., Candolfi-Vasconcelos and Koblet, 1990;Edson et al, 1995;Petrie et al, 2000;Whiting and Lang, 2004). In grapes, secondary and tertiary buds are known to produce fewer and smaller clusters than do primary buds (Pratt, 1974).…”
Section: Resultsmentioning
confidence: 80%
“…Nitrogen is the most important element for maintaining growth and high productivity in tree fruits (Titus and Kang, 1982). Sweet cherries (Prunus avium L.) on precocious, interspecific (P. cerasus · P. canescens) Gisela Ò (Gi) rootstocks (e.g., Gi3, Gi5, Gi6, Gi12) are likely to produce large crops but small-sized fruit when total leaf area is not adequate to support such crop loads (Andersen et al, 1999;Lang, 2000;Whiting and Lang, 2004). When root uptake of N is limited in early spring by cold soils and low canopy transpiration rates (Zavalloni, 2004), the restricted availability of N for growth may contribute to unfavorable leaf area-to-fruit ratios.…”
mentioning
confidence: 99%
“…Indeed, Whiting et al (2005) reported 2-to 6-fold higher yields and reduced fruit quality of 'Bing' sweet cherry grown on 'Gisela 5' and 'Gisela 6' rootstocks, compared to the industry standard, Mazzard (P. avium). However, Whiting and Lang (2004a) showed that high quality 'Bing' sweet cherries can be grown on 'Gisela 5' when fruit number per tree is balanced with the vegetative capacity to supply photoassimilates. Indeed, a negative relationship exists between sweet cherry canopy fruit-to-leaf area ratio (F:LA) and fruit quality Whiting and Lang, 2004a), irrespective of rootstock.…”
mentioning
confidence: 99%
“…However, Whiting and Lang (2004a) showed that high quality 'Bing' sweet cherries can be grown on 'Gisela 5' when fruit number per tree is balanced with the vegetative capacity to supply photoassimilates. Indeed, a negative relationship exists between sweet cherry canopy fruit-to-leaf area ratio (F:LA) and fruit quality Whiting and Lang, 2004a), irrespective of rootstock. Earlier reports also have documented poor quality fruit harvested from heavily cropped sweet cherry trees (Proebsting, 1990;Proebst-ing and Mills, 1981) and similar relationships have been reported for apple (Malus ×domestica Borkh.)…”
mentioning
confidence: 99%
See 1 more Smart Citation